2022
DOI: 10.3390/ijms232415760
|View full text |Cite
|
Sign up to set email alerts
|

miR-193b-3p Promotes Proliferation of Goat Skeletal Muscle Satellite Cells through Activating IGF2BP1

Abstract: As a well-known cancer-related miRNA, miR-193b-3p is enriched in skeletal muscle and dysregulated in muscle disease. However, the mechanism underpinning this has not been addressed so far. Here, we probed the impact of miR-193b-3p on myogenesis by mainly using goat tissues and skeletal muscle satellite cells (MuSCs), compared with mouse C2C12 myoblasts. miR-193b-3p is highly expressed in goat skeletal muscles, and ectopic miR-193b-3p promotes MuSCs proliferation and differentiation. Moreover, insulin-like grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Insulin-like growth factor-2 mRNA-binding protein 1 ( IGF2BP1 ) is an IGF2BP that plays a major role in RNA transport, translation, and stability and regulates cell proliferation and differentiation as an N6-methyladenosine (m6A) reader. Knockout of IGF2BP1 in mice led to dwarfism, intestinal mucosa, and actin mRNA dysregulation and disorganization in the developing neocortex. Evidence from genome-wide association studies and pangenomes revealed that mutations in the promoter region of IGF2BP1 were significantly associated with body size, carcass weight, leg weight, and growth rate. , In a recent study, miR-193b-3p promoted the proliferation of goat skeletal muscle satellite cells by activating IGF2BP1. In addition, IGF2BP1 can promote cancer progression by modulating the mRNA stability of a series of target genes ( IGF2 , ACTB , and CTNNB1 ) . These results suggest that IGF2BP1 is essential for cell proliferation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Insulin-like growth factor-2 mRNA-binding protein 1 ( IGF2BP1 ) is an IGF2BP that plays a major role in RNA transport, translation, and stability and regulates cell proliferation and differentiation as an N6-methyladenosine (m6A) reader. Knockout of IGF2BP1 in mice led to dwarfism, intestinal mucosa, and actin mRNA dysregulation and disorganization in the developing neocortex. Evidence from genome-wide association studies and pangenomes revealed that mutations in the promoter region of IGF2BP1 were significantly associated with body size, carcass weight, leg weight, and growth rate. , In a recent study, miR-193b-3p promoted the proliferation of goat skeletal muscle satellite cells by activating IGF2BP1. In addition, IGF2BP1 can promote cancer progression by modulating the mRNA stability of a series of target genes ( IGF2 , ACTB , and CTNNB1 ) . These results suggest that IGF2BP1 is essential for cell proliferation.…”
Section: Discussionmentioning
confidence: 94%
“…39,40 In a recent study, miR-193b-3p promoted the proliferation of goat skeletal muscle satellite cells by activating IGF2BP1. 41 In addition, IGF2BP1 can promote cancer progression by modulating the mRNA stability of a series of target genes (IGF2, ACTB, and CTNNB1). 42 These results suggest that IGF2BP1 is essential for cell proliferation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Different cell types and different patient groups may be the reason for the difference in the results of the studies. There are many studies in the literature that miR-193b-3p is associated with tumor progression [33,34] and in ammation [9,35]. On the other hand, there are many studies examining the status of this miRNA in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%